The emerging digital future : an overview of broadband and multimedia networks - Morley, John, 1949-; Gelber, Stan. (Danvers, Mass. : Boyd and Fraser, 1998)
Converging realities. Emerging issues. Networks today. Choosing a carrier. Choosing communication services. Connectivity. Frame relay. ATM and STM (asychronous and synchronous transfer modes)...
Keywords: Multimedia systems; Digital communications; Broadband communication systems; Multimedia systems; Digital communications; Broadband communication systems